PANDANGAN TOKOH AGAMA TERHADAP PERNIKAHAN DINI AKIBAT HAMIL PRA NIKAH DI KOTA KENDARI - Kartini Kartini (Institut Agama Islam Negeri Kendari, 2016)
AbstractThis study examines the views of religious leaders against early marriage due to pregnancy before marriage. The primary data is theory of early marriage, interviews to Muslim religious leaders and people who practice early marriages, while secondary data is books and other documentation materials that are associated with research studies. The result is include three parts, namely, the phenomenon of early marrige in Kendari city, that base on surveys and interviews is aquite alarming and needs serious treatment and also need the cooperation of all parties. While the views of religious leaders that that early marriages are permitted in case on didn’t cause the big unadvantage, but if unadvantge is more, it is forbidden. According to religious leaders in the city of Kendari, early mrriage is forbidden, because it got more unadvantage rather that advantage. As for the issue of pregnant before marriage, the religious leaders agreed to sy that it is forbidden and on the question of the legitimacy of their marriage, there is a difference opinion, some argue should be married because of various considerations.Key Words: religious leaders, early marriage, pragnance before marriageAbstrakPenelitian ini mengkaji tentang pandangan tokoh agama terhadap pernikahan dini akibat hamil pra nikah. Data primer dari penelitian ini adalah teori tentang pernikahan dini dan hasil wawancara dari para tokoh agama Islam serta pihak pihak yang melakukan pernikahan dini, sedangkan data sekunder adalah buku buku dan bahan dokumentasi lain yang ada hubunganya dengan kajian penelitian. Hasilnya adalah meliputi tiga bagian yaitu, fenomena pernikahann dini dikota kendari berdasarkan hasil survey, dan wawancara fenomena pernikahn dini di kota kendari cukup memprihatinkan, dan perlu penanganan yang serius dan kerja sama dari semua pihak. Sementara pandangan para tokoh agama bahwa bahwa pernikahan dini dibolehkan sepanjang tidak menimbulkan kemudaratan, tapi jika kemudaratanya lebih banyak dibandingkan kemaslahatanya maka diharamkan, Adapun persoalan hamil pranikah terutama bagi perempuan yang masih dibawa umur para tokoh agama sepakat berpandangan bahwa hamil diluar nikah adalah haram, mengenai persoalan sah tidaknya pernikahan mereka, terjadi perbedaan pendapat, diantara para tokoh agama sebagian berpendapat boleh dinikahkan karena berbagai pertimbangan.Kata Kunci: tokoh agama, pernikahan dini, hamil pra nikah